Prevalence of Giardia Lamblia among Food Handlers and Day-Care Workers in Tehran - Delaram Dargahi; Mitra Zare Bavani; Nahid Einollahi; Nasrin Dashti; Mostafa Rezaeian; Sakineh Abbasi (Tehran University of Medical Sciences, 2017)
Background and Aim: Giardiasis is the most common pathogenic gastrointestinal parasite worldwide and transmitted by ingesting parasite cyst, through water and food and person-to-person contact. Therefore in food handlers and child care workers it is of high importance. In this study we surveyed the job of individuals with giardiasis. Materials and Methods: This study was a pilot descriptive-analytic study. Hundred and nine stool samples were collected from individuals referred to medical centers affiliated to Tehran University of Medical Sciences for health certificate.  Samples were examined with wet mount smear and formol-ether concentration methods. Also a questionnaire was given to each individual. Results: Sixty nine samples were infected with Giardia lamblia. among positive samples for Giardia lamblia 25 (36.23%) were related to food handlers and occupations which are most  frequently associated with food, one (1.44%) nurse, one (1.44%) managing director of the nursery, two (2.89%) housekeepers  and one servant (1.44%). Conclusion: Person-to-person Giardia lamblia transmission is often associated with poor hygiene and sanitation, most commonly by food handlers. Also, day- care workers have a higher risk of infecting children attending day-care centers. Therefore particular attention should be paid to health of this workers as well as three times stool examination.